INVESTIGATING PARAGRAPH OF INDONESIAN EFL STUDENTS’ ESSAY: EFFECTIVE OR INEFFECTIVE - Yenni Arif Rahman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
The term ‘effective paragraph’ refers to the presence of its four building elements i.e. unity, coherence, topic sentence, and sufficient development. Related to that, this study investigates students’ essays whether they consist of effective paragraphs or dominated by the ineffective ones and whether those building elements consistently present in every paragraph. To answer those two questions, this study employs the content analysis method in which it is a particular method to analyze the texts. As the samples are the students’ essays of English major. The result shows that 36 of 76 (47 %) are effective paragraphs and the rest 41 (53 % ) are ineffective which means that more than a half of paragraphs are ineffective. Then it is also revealed there are 62 paragraphs have topic sentence (33%), 49 have proper sufficient developments (26%), 41 of them have unity (23 %), and 30 paragraph are written with coherence (16 %). From the result it can be inferred that most of students’ paragraph are ineffective.